CONTRACEPTIVE SWITCHING PATTERN AMONG MARRIED WOMEN IN EAST JAVA (Proceedings of the International Conference on Public Health, 2017)
Switching of contraceptive methods contributes to high unplanned pregnancy rates, if the switching of contraceptive methods not rational, effective and efficient. Basic Health Research Data (2010), still found 49.4% of women in Indonesia who have more than 3 children, but still using short-term contraceptive methods. If there is no discipline in the use, short-term contraceptive use will be a risk of failure. In addition, problems that occur at the onset of switching methods are also at risk of increasing unwanted pregnancies. This is due to the inaccuracy of process switching methods (Steel & Diamond, 1999). The aims of this study was to analyze the suitability of switching contraceptive method based on age, contraceptive purposes and number of children. This Cross- Sectional study was conducted on 4705 married women. The results showed that 84.4% of women had incompatible patterns of switching of contraceptive methods. 67.4% of women over the age of 35, 57.9% of women who aim to limit their pregnancies, and 68.9% of women with two or more children switched to other contraceptive methods, but still in the non-long-term method category. Perceptions of contraceptive cost is the most dominant factor affecting the incompatible patterns of switching of contraceptive methods. Meanwhile, the source of services is a confounder factor in the relationship between perceptions of contraceptive costs and incompatible patterns of switching of contraceptive methods. Women who want to change contraceptive methods need accurate advice from the health providers about contraceptive method to make effective choices.
Keywords: Contraceptive Switching, Contraceptive Method, Pattern Switching, Rational Contraception